Roland Humphrey is wearing a what? - Kiernan-Johnson, Eileen (Huntley Rahara Press, 2012)
Roland Humphrey is a little boy who likes sparkly things and bright colors. He likes both sports and ballet, and doesn't understand why girls can like both but not boys. Will he bow to peer pressure, or follow his heart and be the authentic Roland Humphrey?